2021
DOI: 10.1515/dx-2021-0016
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on the current state of pre-clerkship clinical reasoning instruction in United States medical schools: a survey of clinical skills course directors

Abstract: Objectives Clinical reasoning skills are essential for sound medical decision-making. Though many have suggested that clinical reasoning instruction should begin in pre-clerkship curricula, neither pre-clerkship clinical skills director perspectives nor extent of instruction is known. This survey study serves as part of a needs assessment for United States medical school pre-clerkship clinical reasoning curricula. Methods Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Some facets of the diagnostic process—namely history taking, physical examination, and rudimentary differential diagnosis—are standard components of the pre-clerkship curriculum. In recent years, directors of clinical skills courses have begun to incorporate other aspects of clinical reasoning into their pre-clerkship courses [ 12 ]. One study of internal medicine clerkships suggested that clinical reasoning education is more ‘caught’ (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Some facets of the diagnostic process—namely history taking, physical examination, and rudimentary differential diagnosis—are standard components of the pre-clerkship curriculum. In recent years, directors of clinical skills courses have begun to incorporate other aspects of clinical reasoning into their pre-clerkship courses [ 12 ]. One study of internal medicine clerkships suggested that clinical reasoning education is more ‘caught’ (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The DOCS institutional representative response rate was 69% (102/148) of targeted respondents answering 1 or more survey items. More detailed respondent demographics have been previously reported [ 15 ]. This overall response rate for the clerkship leaders survey was 19% (305/1859) and ranged from 3% to 30% across specialties.…”
Section: Resultsmentioning
confidence: 99%
“…The authors previously reported separately on cross-sectional surveys of pre-clerkship clinical skills course directors serving as institutional representatives to the DOCS organization, and clerkship leaders (clerkship directors and co-directors, associate clerkship directors, and clerkship clinical site directors) from organizations that comprise ACE [ 15 , 16 ]. This report represents the analysis comparing the results from these two surveys.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 9 14 ].). Moreover, teachers are often not trained to explicitly teach CR, including explaining their own reasoning to others [ 10 12 ] although this appears to be an important factor in the implementation of a CR curriculum [ 15 ]. Some teachers even question whether CR can be explicitly taught [ 16 ].…”
Section: Introductionmentioning
confidence: 99%